Scientific literacy and Science teaching in Basic Education: panorama in the context of Brazilian academic research in the last five years of ENPEC (Research, Society and Development, 2020)
This study aimed to analyze 32 manuscripts from three editions (2015, 2017 and 2019) of the National Research Meeting in Science Education (ENPEC), on the contributions, advances and/or weaknesses of pedagogical actions related to Scientific Literacy (AC) in the Teaching of Basic Education Sciences (EC). It is an exploratory research based on a systematic review of the literature, with analysis of the level of education; region; didactic proposal; contributions and categorization in thematic axes (established after the full reading of the works). The research results indicate that most of the manuscripts were aimed at High School and absence from EJA. It is understood that Elementary and High School are considered locus for the realization of CA, in which the diversification of methodological strategies can help in the development of competencies that involve CA. It is concluded that the plurality of didactic actions presented in the manuscripts selected for this study, emphasize the CA approach in Basic Education, enabling the use of technologies, construction of didactic materials and didactic sequences based on Science, Technology, Society and Environment (CTSA) for every space and school level.